Skrining Bioaktivitas Ekstrak Kulit Akar Bakau Merah (Rhizophora apiculata bl.) Terhadap Daya Hambat Pertumbuhan Koloni Bakteri Streptococcus sp. - Darlian, Lili (Jurnal Progres Kimia Sains, 2011)
The research to determine the bioactivity of the root bark of Rhizophoraapiculata extract on the inhibition of the growth of colonies of bacteria Streptococcussp was carried out. Roots of Rhizophora apiculata bark extract is obtained byextraction by maceration and liquid-liquid partition using solvents methanol and thesolvent of n-hexane, chloroform, and ethyl acetate, respectively. Bioactivity testingagainst bacterial colony growth of Streptococcus sp. performed using the agar diffusionmethod on media nutrient agar. The results showed that extracts of n-hexane,chloroform extract and ethyl acetate extract of the root bark of Rhizophora apiculatawere impregnated on paper discs can form a clear zone around it. This indicates that theroots of Rhizophora apiculata bark extract could inhibit the growth of colonies ofbacteria Streptococcus sp. Greatest inhibition zone diameter derived from the ethylacetate fraction of 2.90 mm, followed by a 1:03 mm from the chloroform fraction, andby 0:47 mm fraction of n-hexane.